Interface Engineering and Direct Observation of Strengthening Behavior in Field‐Sintered Boron Nitride Nanotube–Magnesium Alloy Composite. Issue 7 (17th April 2020) - Nautiyal, Pranjal; Denis, Noemie; Dolmetsch, Tyler; Zhang, Cheng; Boesl, Benjamin; Agarwal, Arvind
Abstract : Boron nitride nanotube (BNNT) is integrated in AZ31 magnesium alloy by field‐assisted powder metallurgy route. A mat of BNNT is sputter‐coated with pure Mg and then sandwiched between AZ31 alloy powders. This layered composite is consolidated by spark plasma sintering (SPS). A high processing pressure of 400 MPa aids in intimate alloy–nanotube adhesion due to localized deformation. Thermal diffusion between AZ31 and BNNT (at 400 °C sintering temperature) results in the formation of Mg3 N2 and AlN nanophases at the interface. Due to ultrafast Joule heating during SPS, the reactions are kinetically controlled, and only trace amounts of products are formed without compromising the characteristics of the nanotubes. The interphases aid in reactive bonding between AZ31 and BNNT, which is essential for load‐bearing applications. In situ double cantilever loading of the composite inside the scanning electron microscope shows that the nanotubes bridge, resist, and delay crack propagation. These findings demonstrate the promise of thermally stable BNNTs as reinforcement for engineering lightweight Mg‐based structural composites. Abstract : Boron nitride nanotube (BNNT) is used as the reinforcement phase for engineering a lightweight metal‐matrix composite based on AZ31 magnesium alloy. The composite is fabricated by sputtering and spark plasma sintering. Limited interfacial reactions between BNNT and AZ31 during processing aid in reactive bonding. In situ imaging of mechanical deformation demonstrates the efficacy of BNNTs to resist crack propagation.